P230 Investigating the role of chest physiotherapy in the collection of sputum samples from individuals with cystic fibrosis (CF). (12th November 2015) - Dacie, R; Howlin, R; Carroll, M; Connett, G
Abstract : Introduction: Chronic respiratory infection is responsible for the majority of the morbidity and mortality of CF patients. In order to guide treatment regimes and improve understanding of the pathophysiology of CF, airway secretions are sampled and analysed. Sputum is usually the selected method of sampling. Often, large quantities of sputum are required to facilitate comprehensive laboratory testing. Hence, when designing studies, it is important to consider the quantity of sputum likely to be produced by patients and to ensure that the composition of the sputum samples is not altered by the procedure by which they are obtained. This study aimed to investigate the effect of chest physiotherapy on the quantity and composition of sputum samples collected from individuals with CF. It was hypothesised that physiotherapy would increase the quantity of sputum produced, reduce the salivary content and alter the microbiological content. Methods: Clinically stable adults with CF were recruited at outpatient clinics and randomised into group A (physiotherapy group, n = 21) or group B (no physiotherapy group, n = 25). Laboratory processing of the samples involved determining sample weights and counting human cells (alive respiratory cells, dead respiratory cells and squamous cells). The dissolved sputum was also transferred onto plates of cetrimide agar for culturing Pseudomonas aeruginosa . Colony-forming units (CFUs) were counted on the plates after 24 h. Results: Samples from the physiotherapy group had significantly greater weights than the no physiotherapy group (p < 0.001). When considering the total number of cells per gram of sputum, there was no statistical difference between the two groups (p = 0.396). However, the numbers of squamous cells per gram, and dead respiratory cells per gram were both significantly greater in the no physiotherapy group (p = 0.039 and p = 0.001 respectively). There were no significant differences between numbers of alive respiratory cells per gram (p = 0.487) or CFUs (p = 0.459). Conclusion: Whilst physiotherapy was found to increase the quantity of sputum collected, there were significant differences in sputum composition, suggesting that the two groups represent samples from different niches. Hence, when planning a study involving sputum analysis, the procedure by which the sample is obtained has to be considered when interpreting the results.